Chemical-free saturated steam pretreatment of oil palm empty fruit bunch for improved enzymatic saccharification - Shamsudin, Saleha; Kamal Bahrin, Ezyana; Hassan, Mohd Ali; Shirai, Yoshihito (Taylor and Francis Ltd., 2024)
Oil palm empty fruit bunch (EFB) as the main lignocellulosic residue from the oil palm industry serves as suitable feedstock for enzymatic saccharification, yielding fermentable sugars. Due to complex inter-association between hemicellulose, cellulose and lignin within EFB lignocellulosic matrix, different saturated steam conditions at 140-230 °C, 0.3-2.3 MPa was chosen as a pretreatment strategy, targeted to hydrolyze hemicellulose and reduce crystallinity of cellulose to enhance enzymatic saccharification which need no chemical requirement and potential for energy recovery. As a result, SEM analysis of EFB morphology indicated that the enhanced silica body removal from 190-230 °C of saturated steam pretreatment correspondingly led to substantial 82 removal of hemicellulose. Consequently, enzymatic saccharification yielded between 0.621-0.637 g glucose per g EFB, equivalent to 93-95 of cellulose saccharification by Acremonium cellulase on EFB treated with saturated steam at 210-230 °C. Notably, a short duration pretreatment of EFB at 210 °C for 2 min was proved sufficient for high fermentable sugar production. The potential energy estimated for employing saturated steam pretreatment of EFB in a palm oil mill was sufficient by 2.2 x 1012 kJ/year.